Transfer pricing risk management of intangible assets for multinational enterprises (MNEs) - Shao, Cong (2024)
This study explores transfer pricing risk management of intangible assets for multinational enterprises (MNEs). Transfer pricing is a controversial area, often involving the pricing of assets/goods/services sold or transferred between group companies, for which there is no external market and thus no market price. The pricing of transactions across international borders can mean that costs/income/profits, etc., can be attributed to higher/lower tax rate countries where MNEs have operations and so may not necessarily reflect the economic reality of intra-group transactions. The abuse of transfer pricing by some MNEs allegedly causes countries to lose billions in revenue, thereby forcing tax administrations to tighten regulations. However, with the constantly updated regulations, especially the Organisation for Economic Co-operation and Development (OECD) Base Erosion and Profit Shifting (BEPS) project, MNEs now must expend considerable effort and expense so as to be considered tax-compliant. Transfer pricing, therefore, has become a potential tax-compliance risk/burden. Because of certain factors associated with intangible assets (e.g., uncertainty, exclusivity, etc.), transfer pricing of such assets is now regarded as an especially challenging topic. Managing transfer pricing risks relating to intangibles is therefore of practical importance for MNEs. However, there are relatively few academic papers discussing this issue, and transfer pricing risk management of intangibles is, therefore, an important but under-researched research area. In order to contribute to the area, the thesis provides insights into how to manage transfer pricing risks concerning intangible assets.